The perception of foreigners and jews in Germany: a structural analysis of a large opinion survey - Fertig, Michael; Schmidt, Christoph M. (Discussion paper series, 2002)
The ultimate aim of opinion surveys is the provision of information on the distribution of preferences and perceptions at the individual level. Yet, eliciting this information from the data is typically difficult. This paper uses a structural model to explain the answers on a set of questions regarding the perception of foreigners and Jews by native Germans. In this model it is assumed that in addition to observable individual characteristics there exists an underlying unobserved attitude towards minorities which drives the distribution of answers by native respondents. This latent variable in turn is assumed to be influenced by a set of observable socio-economic characteristics of the individuals. In order to estimate this model it is necessary to impose strong identification restrictions. Estimation results show that education is the key correlate of the perception of foreigners and Jews in Germany.
Keywords: Germany -- Ethnic relations; Germany -- Social conditions -- 1990-; Graue Literatur; Arbeitspapier